Data Protection Using Digital Watermarking (International Journal of Engineering and Computer Science, 2013)
— Digital watermarks allow information about the owner, usage rights and more to be permanently attached to the content. Watermarking is the art and science of communicating in such a way that the presence of a message cannot be detected. Simply steganographic techniques have been in use for hundreds of years, The other major area of copyright marking, where the message to be inserted is used to assert copyright over a document can be further divided into watermarking and fingerprinting. Digital watermarking has been proposed as a solution to the problem of copyright protection of multimedia data in a networked environment. It makes possible to tightly associate to a digital document a code allowing the identification of the data creator, owner, authorized consumer, and so on